Marketing Strategy Of Jeruju (Acanthus Ilicifolius) Tea Products In Harapan Mandiri, Kebumen, Central Java - Adi, Catur Pramono; Soeprijadi, Lilik; Aripudin, Aripudin; Arifiana, Alya Nida Marbella (Barakuda 45: Jurnal Ilmu Perikanan dan Kelautan, 2023)
The problem that Harapan Mandiri is facing is the lack of consumer buying interest in original Jeju tea products. For this reason, Harapan Mandiri is able to change this condition through product innovation using additional ingredients such as ginger and rosella flowers in the hope of attracting consumer interest. The purpose of this research is to make innovative products to increase sales turnover. The results of the study show the following business analysis: With an investment cost of 6,032,000, fixed costs 2,060,000, variable costs 4,660,000, total expenses 6,720,000/month, revenue costs Rp. 15,000,000, profit/loss Rp. 7,240,000, R/C ratio 2.07, B/C ratio 1.07, BEP price 6,720, BEP production 265 packs. The marketing strategy carried out by Harapan Mandiri in developing its business products is by promoting products more frequently to various community association forums so that people are more familiar with Jeju tea products with the addition of ginger and rosella flowers, always updated with the times so as not to be left behind by market competition. by developing flavor variants in tea and updating packaging to make it more attractive to consumers' purchasing power, collaborating with partnerships so that they can increase marketing relations and collaboration in advancing business and building public trust by maintaining quality taste and product quality.